2017
DOI: 10.1083/jcb.201704071
|View full text |Cite
|
Sign up to set email alerts
|

Cobl-like promotes actin filament formation and dendritic branching using only a single WH2 domain

Abstract: Local actin filament formation powers the development of the signal-receiving arbor of neurons. In this study, Izadi et al. demonstrate that Cobl-like, which bears only a single WH2 domain, mediates dendritic branching by coordinating with the F-actin–binding protein Abp1 in a Ca2+/CaM-controlled manner to control actin dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…In contrast, both PHLDB2 and COBLL1 are highly expressed in COL22A1 and CARM1P1 t-types, with PHLDB2 displaying slightly more specific enrichment of expression in these t-types. COBLL1 is a morphogenesis-associated gene that has been shown to promote dendrite branching and the formation of actin filament membrane ruffles 45 . Similarly, PHLDB2 localizes to dendritic spines of hippocampal neurons where it plays an important role in regulation of long-term potentiation by affecting the density of glutamate receptors, and knockout of this gene impairs the formation of memories in mice 46 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, both PHLDB2 and COBLL1 are highly expressed in COL22A1 and CARM1P1 t-types, with PHLDB2 displaying slightly more specific enrichment of expression in these t-types. COBLL1 is a morphogenesis-associated gene that has been shown to promote dendrite branching and the formation of actin filament membrane ruffles 45 . Similarly, PHLDB2 localizes to dendritic spines of hippocampal neurons where it plays an important role in regulation of long-term potentiation by affecting the density of glutamate receptors, and knockout of this gene impairs the formation of memories in mice 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Primary rat hippocampal neuronal cells for immunofluorescence analyzes were cultured and maintained as described previously [ 30 , 31 , 32 ]. Briefly, neurons dissociated from hippocampi of E18 rats were seeded at a density of 60,000/well (24-well plate).…”
Section: Methodsmentioning
confidence: 99%
“…The actin nucleator Cobl and its evolutionary ancestor protein Cobl-like are molecularly quite distinct ( Figure 1–figure supplement 1 ), however, both critical for dendritic arbor formation (Ahuja et al, 2007; Izadi et al, 2018). Side-by-side loss-of-function analysis of both factors in developing primary hippocampal neurons using IMARIS software-based evaluations for detailed analyses of the elaborate morphology of such cells (Izadi et al, 2018) revealed surprisingly similar phenotypes ( Figure 1A-G ). Dendritic branch and terminal point numbers as well as total dendritic length all were severely affected by lack of Cobl-like ( Figure 1A-G ).…”
Section: Resultsmentioning
confidence: 99%
“…We next addressed whether the identified Cobl-like interaction partner syndapin I would indeed be critical for Cobl-like’s functions. GFP-Cobl-like massively promoted dendritic arborization already after very short times (Izadi et al, 2018). Strikingly, all Cobl-like gain-of-function phenotypes in developing primary hippocampal neurons were completely suppressed upon syndapin I RNAi ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation